2005
DOI: 10.1359/jbmr.041222
|View full text |Cite
|
Sign up to set email alerts
|

Bone Adaptation to a Mechanical Loading Program Significantly Increases Skeletal Fatigue Resistance

Abstract: Using a mechanical loading program to induce bone adaptation, we found that small (<2-fold) changes in the structural properties of the rat ulna increased its fatigue resistance >100-fold. This indicates that a moderate exercise program may be an effective preventative strategy for stress fractures.Introduction: There are currently limited preventative strategies for stress fractures. Because stress fracture risk is directly influenced by skeletal properties, it has been hypothesized that modification of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 46 publications
4
129
0
2
Order By: Relevance
“…The findings from animal models are corroborated, to a certain extent, in human studies that report increased areal bone mineral density following high impact exercise [14][15][16][17] Areal BMD is not a suitable surrogate measure of bone strength with exercise interventions [18] since animal studies report large changes in bone strength despite only modest changes in density [1,19]. This is supported in cross-sectional studies of athletes using peripheral Quantitative Computed Tomography (pQCT), which describe a thicker cortex in the playing arm of tennis players [20], the tibia of triple jumpers [21] and in athletes from impact sports [22] compared with matched controls, with little or no differences in density [23].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The findings from animal models are corroborated, to a certain extent, in human studies that report increased areal bone mineral density following high impact exercise [14][15][16][17] Areal BMD is not a suitable surrogate measure of bone strength with exercise interventions [18] since animal studies report large changes in bone strength despite only modest changes in density [1,19]. This is supported in cross-sectional studies of athletes using peripheral Quantitative Computed Tomography (pQCT), which describe a thicker cortex in the playing arm of tennis players [20], the tibia of triple jumpers [21] and in athletes from impact sports [22] compared with matched controls, with little or no differences in density [23].…”
Section: Introductionmentioning
confidence: 76%
“…These changes are achieved through the complex orchestration of bone modelling/remodelling [2][3][4], partly mediated by osteocyte signalling [5,6] Studies using the rat ulna have unravelled the osteogenic stimuli of mechanical loading, confirming that bone is most responsive to dynamic loading [1,7], high strain rates [8][9][10] unfamiliar strain distributions [11], and to discrete rather than continuous bouts of loading [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11), a fatigue test might be a more meaningful indicator of whether the bone has recovered its normal function or is susceptible to reinjury. For example, Warden et al 12 used fatigue testing of the rat ulna to demonstrate that bone ''adaptation'' to a 5 week mechanical loading program improved ulnar function by increasing its fatigue life by &100-fold. To our knowledge, there has been no comparable assessment of fatigue behavior after bone ''repair'' following a stress fracture.…”
Section: Introductionmentioning
confidence: 99%
“…(20,21) Such mechanical change can be sensed by osteocytes and osteoblasts, (22,23) which initiate periosteal apposition preferentially where the highest strains exist. (24,25) Accordingly, in this analysis the most significant difference in bone mass between 18-year-old girls and their mothers was found in the anterior region. This indicated that bone mass accrual from early adulthood to middle age is direction specific, corresponding with the change of strains.…”
Section: Discussionmentioning
confidence: 64%